2020
DOI: 10.2147/ijn.s257711
|View full text |Cite
|
Sign up to set email alerts
|

<p>Exploring the Interaction of Cobalt Oxide Nanoparticles with Albumin, Leukemia Cancer Cells and Pathogenic Bacterial by Multispectroscopic, Docking, Cellular and Antibacterial Approaches</p>

Abstract: The interaction of NPs with biological systems may reveal useful details about their pharmacodynamic, anticancer and antibacterial effects. Methods: Herein, the interaction of as-synthesized Co 3 O 4 NPs with HSA was explored by different kinds of fluorescence and CD spectroscopic methods, as well as molecular docking studies. Also, the anticancer effect of Co 3 O 4 NPs against leukemia K562 cells was investigated by MTT, LDH, caspase, real-time PCR, ROS, cell cycle, and apoptosis assays. Afterwards, the antib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 71 publications
(83 reference statements)
2
11
0
Order By: Relevance
“…Although chitosan-coated nanoparticles are insoluble under normal physiological pH, the concentration should be less than 100 µg/mL when used in biomedicine for safety reasons [58]. This is consistent with the experimental results of Arsalan N et al who also proved that Co 3 O 4 NPs can reduce the survival rate of K562 cells by damaging cell membrane, activating caspase-9, -8 and -3, increasing Bax/Bcl ratio and promoting ROS production, cell cycle arrest and apoptosis and do not affect the survival rate of normal lymphocytes [59].…”
Section: Selective Cancer Cell Inhibition By Cobalt Oxide Nanoparticlessupporting
confidence: 88%
See 1 more Smart Citation
“…Although chitosan-coated nanoparticles are insoluble under normal physiological pH, the concentration should be less than 100 µg/mL when used in biomedicine for safety reasons [58]. This is consistent with the experimental results of Arsalan N et al who also proved that Co 3 O 4 NPs can reduce the survival rate of K562 cells by damaging cell membrane, activating caspase-9, -8 and -3, increasing Bax/Bcl ratio and promoting ROS production, cell cycle arrest and apoptosis and do not affect the survival rate of normal lymphocytes [59].…”
Section: Selective Cancer Cell Inhibition By Cobalt Oxide Nanoparticlessupporting
confidence: 88%
“…Human serum albumin (HSA) is the most abundant protein in plasma and is often used to carry a variety of drugs to meet various treatment requirements. After Arsalan et al used different concentrations of Co3O4 NPs to interact with HSA molecules, the fluorescence results show that high concentrations of Co3O4 NPs could change the quaternary structure of HSA but did not affect the natural structure of HAS [59].…”
Section: Cobalt Oxide Nanoparticle Based Drug Delivery Systems For Anticancer Treatmentmentioning
confidence: 99%
“…Blood is often the first physiological environment that NPs interact with after intravenous injection, and plasma contains numerous proteins capable of interacting with NPs and forming a PC [5]. Proteins can be adsorbed to the NP surface in native or denatured forms depending on the inherent stability and hydrophobicity [6][7][8][9]. Some studies have demonstrated that NP-PC interactions regulated cellular targeting and uptake of therapeutic NPs while reducing the effects of unwanted NP cytotoxicity [4,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] In particular, Co oxides can be used as catalysts, 4,5 gas sensors, 6 and in the development of magnetic recording media. 7 Moreover, Co oxide nanoparticles are candidates to inhibit cancer cell growth 8,9 and have great potential as antimicrobial agents. 2,8 More specifically, there is a lot of interest in magnetic nanoparticles because they are promising candidates for diverse applications such as drug delivery, tissue engineering, biosensing, magnetic resonance imaging, ultrahigh density data storage, and magneto-electric memory devices.…”
Section: Introductionmentioning
confidence: 99%
“…7 Moreover, Co oxide nanoparticles are candidates to inhibit cancer cell growth 8,9 and have great potential as antimicrobial agents. 2,8 More specifically, there is a lot of interest in magnetic nanoparticles because they are promising candidates for diverse applications such as drug delivery, tissue engineering, biosensing, magnetic resonance imaging, ultrahigh density data storage, and magneto-electric memory devices. 10 Also, clusters with interesting properties could potentially be assembled into larger nanostructured materials.…”
Section: Introductionmentioning
confidence: 99%